2021 Assessment of New Zealand district health boards' institutional healthy food and drink policies: the HealthY Policy Evaluation (HYPE) study - Gerritsen S; Kidd B; Rosin M; Shen S; Mackay S; Te Morenga L; Mhurchu CN (Pasifika Medical Association Group (PMAG), 2022)
AIM: To assess adoption of the voluntary National Healthy Food and Drink Policy (NHFDP) and the alignment of individual institutional healthy food and drink policies with the NHFDP. METHOD: All 20 district health boards (DHBs) and two national government agencies participated. Policies of those organisations that had not fully adopted the NHFDP were assessed across three domains: nutrition standards; promotion of a healthy food and beverages environment; and policy communication, implementation and evaluation. Three weighted domain scores out of 10, and a total score out of 30 were calculated. RESULTS: Nine of the 22 organisations reported adopting the NHFDP in full. Of the remaining 13, six referred to the NHFDP when developing their institutional policy and three were working toward full adoption of the NHFDP. Mean scores (SD) were 8.7 (1.0), 6.1 (2.6) and 3.8 (2.2) for the three domains, and 18.6 (4.8) in total. Most individual institutional policies were not as comprehensive as the NHFDP. However, some contained stricter/additional clauses that would be useful to incorporate into the NHFDP. CONCLUSION: Since a similar policy analysis in 2018, most DHBs have adopted the NHFDP and/or strengthened their own nutrition policies. Regional inconsistency remains and a uniform mandatory NHFDP should be implemented that incorporates improvements identified in individual institutional policies.
Keywords: Beverages; Government Agencies; Health Policy; Health Promotion; Humans; New Zealand; Nutrition Policy; 11 Medical and Health Sciences